Soluble congeners of prior insoluble shape-persistent imine cages - Holsten, Mattes; Feierabend, Sarah; Elbert, Sven; Rominger, Frank; Oeser, Thomas; Mastalerz, Michael (Chemistry - a European journal, 2021)
One of the most applied reaction types to synthesize shape-persistent organic cage compounds is the imine condensation reaction and it is assumed that the formed cages are thermodynamically controlled products due to the reversibility of the imine condensation. However, most of the synthesized imine cages reported are formed as precipitate from the reaction mixture and therefore rather may be kinetically controlled products. There are even examples in literature, where resulting cages are not soluble at all in common organic solvents to characterize or study their formation by NMR spectroscopy in solution. Here, a triptycene triamine containing three solubilizing n-hexyloxy chains has been used to synthesize soluble congeners of prior insoluble cages. This allowed us to study the formation as well as the reversibility of cage formation in solution by investigating exchange of building blocks between the cages and deuterated derivatives thereof.
Gesehen am 09.03.2022